Study of solid waste disposal system in high-rise buildings between conventional system and Centralize Vacuum System (CVS) / Ahmad Anwar Mohd Zaki - Mohd Zaki, Ahmad Anwar (Faculty of Architecture, Planning and Surveying, 2009)
Rising population in the country, intensive urbanization, coupled with a robust industrial growth, a more affluent population etc. have all contributed to high volume of solid wastes being generated in the country. The increased generation and accumulation of solid waste are being beginning to produce social, economic and environmental problems of significant proportions. Solid wastes are arising from man’s domestic, social and industrial activities is increasing in quantity and variety as a result of this increase in populations, rising standard in living and developments in technology (Michael J. Suess, Solid Waste Management, Selected topics, World Health Organization, 1986, pg. 1) Nowadays many high rise building used various systems as to ensure that the solid waste will disposed with efficient way. Basically this system as to achieve in efficient building management, also comfortable for occupant. Preventing and managing waste in cost, qualities, comfortable, performance, and practicality is at the main point of sustainable development. Waste implies unnecessary depletion of unnecessary costs, and environmental damage. Sustainable waste management is about using resources more efficiently. Solid waste management is a major challenge for Malaysia to achieve Vision 2020 which lays out the direction for Malaysia to become a fully developed nation by 2020, which are presents a challenge to established policies and practices in development of solid waste management especially for high-rise building.